Rekonstruksi Identitas Sosial Melalui Peran Sosial Kecerdasan Buatan Dalam Pembelajaran: Analisis Sistematis Kajian Sosiologi Pendidikan - Henry Anderson Ruagadi (Journal on Education, 2025)
This study aims to analyze the role of Artificial Intelligence (AI) as a social agent in shaping interactions, values, and the social identity construction of learners within digital education. Using a Systematic Literature Review (SLR) of 38 peer-reviewed articles published between 2022 and 2025, this research identifies the conceptual, theoretical, and methodological patterns employed in previous studies. The findings reveal that AI functions not only as a pedagogical tool but also as a social entity that reshapes learning structures and creates new educational habitus. AI-mediated learning fosters digital self-reflection and autonomy but also generates system dependency and shifts traditional social values within education. This study contributes to the field of sociology of education by positioning AI as a social factor mediating the relationship between humans and technology. The findings highlight the necessity of reflective, ethical, and context-aware approaches when integrating AI into future educational systems.